Microwave-enhanced cracking over ZSM-5 (20) catalysts: Taguchi optimization for improved conversion and energy savings - Sulaiman, Muataz M.; Makki, Hasan F. (Edelweiss Applied Science and Technology, 2024)
For heavy naphtha cracking, the combination of microwave irradiation and ZSM-5 (20) catalyst increases conversion and saves energy. The QVF tube reactor is 240 mm long, 12.7 mm inner diameter with an 80 mm effective zone. The feed goes into the reactor after it has been heated, and the reaction takes place in the catalytic zone, where ceramic particles loaded in the bottom and upper regions of the tube help the feed components and products spread out more evenly. All products were condensed and analysed using gas chromatography. The cracking was done under the following conditions: microwave irradiation (750–1250 W), preheating temperatures (150–250 ˚C), and space velocities (2 and 6 l/hr). The microwave radiation generates hot spots in the catalyst structure, which enhance cracking. The best conversion is (66.77%) at a microwave power of 1250 W, a flow rate of 2 l/hr, and a preheating temperature of 200 ˚C. The nitrogen injection increased conversion in all conditions. Conventional techniques are incapable of cracking heavy naphtha within the temperature range of 150-250 ˚C. Generally, an increase in microwave power and preheating temperature leads to an increase in conversion, while a decrease in flow rate, both with and without nitrogen injection, negatively impacts conversion. This study examined the impact of microwave radiation with a catalyst on residence duration, energy efficiency, and conversion at lowered temperatures.